The application and progress of stem cells in auricular cartilage regeneration: a systematic review - Liu, Yu; Wu, Wenqing; Seunggi, Chun; Li, Zhengyong; Huang, Yeqian; Zhou, Kai; Wang, Baoyun; Chen, Zhixing; Zhang, Zhenyu (Frontiers in Cell and Developmental Biology, 2023)
The treatment of microtia or acquired ear deformities by surgeries is a great challenge for plastic and ENT surgeons, one of the significant difficult points is constructing the scaffold of reconstructing auricular. As a type of cell with multiple differentiation potentials, stem cells play an essential role in the construction of cartilage scaffolds, and therefore have received widespread attention in ear reconstructive research Methods: A literature search was conducted for peer-reviewed articles during 2005 and 2023 about following keywords: stem cells; auricular cartilage; ear cartilage; conchal cartilage; auricular reconstruction, regeneration, reparation, chondrocyte; tissue engineering in these databases: PubMed, MEDLINE, Cochrane and Ovid databases.Results: Thirty-three research articles were finally selected and summarized the main characteristics. Adipose-derived stem cell (ADSC), bone marrow mesenchymal stem cell (BMMSC), perichondrial stem/progenitor cell (PPC), and cartilage stem/ progenitor cell (CSPC) were mainly used in chondrocytes regeneration. Injecting the stem cells into the cartilage niche directly, co-culturing the stem cells with the auricular cartilage cells and inducing the cells in the chondrogenic medium in vitro were the main methods that have been demonstrated in the studies.The chondrogenic ability of these cells was observed in vitro, and they also maintained good elasticity and morphology after implantation in vivo for a period.ADSC, BMMSC, PPC, and CSPC were the main stem cells that have been researched in craniofacial cartilage reconstruction, the regenerative cartilage performed highly similar as normal cartilage, and the test of AGA and type II collagen content also proved the cartilage property of the neo-cartilage. However, stem cell reconstruction of the auricle is still in the initial stage of animal experiments, transplantation with such scaffolds in large animals is still lacking, and there is still a long way to go.